Design of Bluetooth Wireless Transporter Mecanum Wheeled Robot with Android Smartphone Controller for Moving Item - Yandhika Surya Akbar Gumilang; Krisdianto Krisdianto; Haitsam Haitsam; Moch. Aditya Rizky Fahreza; Aziz Alfayid (ELKHA : Jurnal Teknik Elektro, 2023)
Technology development are going so fast. One of technology development on purposed reasearch is moving item technology. Moving item can be dangerous works for human. There are some dangerous case of moving item, heavy weight items, hazardous chemical compounds, etc. Purposed research is to minimize risk from previous problem. It can reduce work load energy and minimize an accident in terms of moving items for operator, which are often encountered in the industry sector. Purposed research made bluetooth wireless transporter mecanum wheeled robot with android smartphone controller for moving item. Robot made in prototype scale. Robot size is 28x13x15 cm(s). Robot made based on arduino uno and L293D driver motor shield with android smartphone controller. Using android controller was made user easier to use. This robot design equipped with 4 mecanum wheel (4 DC motors), two 1850 battery, Arduino Uno, L293D driver motor, HC-06 bluetooth module, LCD and two M90s Servos for gripper. Gripper has two motions, shift and lift motions. After several test of purposed transporter robot, it can conclude that purposed transporter robot can controlled wireless with bluetooth from 0 to 20 meters. Purposed robot gripper has two motion Gripper test result, purposed transporter robot can shift item up to 350 grams weight load and lift an item up to 200 grams. Robot can operate up to 128 minutes with full capacity batteries . From several test, main purposed of this robot can provided. It is to moving an item to another place. Purposed robot can implements in industry sector with adjustment specification, but if weight load and dimensions match with this research, then purposed robot can be used properly.